Pengaruh Manajemen Laba, Return on Asset dan Persistensi Laba Terhadap Biaya Modal pada Perusahaan Perbankan - Fitriani, Lisa (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
Profit management is manager effort to get advantages including the effort management to maximize or minimize profit of including flattening of profit as according to desire of management. Profit management can be conducted by comparing working capital akrual with sale conducted by company. Acrual working capital consist of change of circulating assets, change of current lialibilities and also change of cash. Profit management done by company more or less him will influence decision of investor. Because menagement and investor only communicating to pass financial statement released by management. This research aim to to test empirically influence between profit management with cost of capital. In this research is used by return on asset and of persistensi profit as variable control by using data company of banking wich go-public in effect exchange of Jakarta during period of perception three year that is 2003 until 200. The result of research that is management profit of significant equal having an effect on to cost of capital.